Early and late effects of exercise and athletic training on neural mechanisms controlling heart rate - Furlan, R.; Piazza, S.; Dell'Orto, S.; Gentile, E.; Cerutti, S.; Pagani, M.; Malliani, A. (Cardivascular Research, 1993)
Objective: This study addresses the long term and short term effects of heavy dynamic exercise on neural control of heart rate. Methods: A group of healthy controls was compared with (1) a group of trained athletes during a period of yearly rest (detrained) and (2) a group of trained athletes at the peak of their training routine. Additionally, a group of 10 controls was studied 1, 24, and 48 h after a single bout of maximal dynamic exercise. Spectral analysis of RR interval variability provided markers of sympathetic (low frequency, LF, 0.10 Hz) and vagal (high frequency, HF, 0.25 Hz) modulation of the sinoatrial node. Results: (1) In detrained athletes resting bradycardia was accompanied by a predominant HF rhythmic component suggestive of a prevailing vagal tone. (2) Trained athletes showed a resting bradycardia together with high LF values, thus suggesting a more complex neural interaction modulating heart rate. An additional longitudinal part of the study, performed on a group of detrained athletes who were examined for the second time after resuming training, confirmed the finding of a prevailing LF component in resting conditions. (3) In the 10 control subjects maximal dynamic exercise induced an increase in LF which outlasted the cessation of exercise up to 24 h, suggesting a persistent sympathetic activation. (4) Passive tilt, a manoeuvre which enhances sympathetic drive, produced a greater enhancement of the LF component in trained athletes than in control subjects. Conclusions: The cardiac sympathetic excitation outlasting heavy dynamic exercise may explain the coexistence of training bradycardia with signs of enhanced sympathetic activity in trained champion athletes.